THE IMPORTANCE OF FORMING CREATIVITY ICHILDREN (International journal of artificial intelligence, 2025)
This article is about the formation of creativity in elementary school students, the development of creative and logical thinking in them, and teaching them to create news based on their acquired knowledge. Along with them, the article also provides information about the concept, content and essence of creativity.